Influence of staining on the optical properties and surface topography of low-shrinkage and conventional dental composites - Dervišević, Milica; Dramićanin, Miroslav; Todorović, Aleksandar; Lazić, Zoran; Manojlović, Dragica (Vojnosanitetski pregled, 2025)
Background/Aim. Matching the optical properties of composite restorations and teeth is very important in esthetic dentistry. The challenge lies not only in the initial matching but also in the fact that these optical properties change significantly in the oral environment over time. The aim of the study was to examine the initial color, translucency, fluorescence, and surface topography of various composite materials, their changes after seven days of immersion in tea, as well as after repolishing. Methods. Two low-shrinkage nanohybrid composites (N’Durance® and Charisma® Diamond) and two conventional composites [Tetric EvoCeram® (nanohybrid) and Gradia® Direct (microhybrid)] in shade B1 were immersed in tea for seven days. Diffuse reflection, fluorescence, and surface roughness were measured before and after immersion in tea, as well as after repolishing. Color and translucency were calculated using the CIEDE2000 and CIEDTP2000 equations. Results. The highest initial lightness (L*) values were observed for Charisma® Diamond, while the highest red-green (a*) and yellow-blue (b*) coordinates were observed for Tetric EvoCeram®. The following trend in color change (∆E00) was observed: Tetric EvoCeram®>N’Durance®>Charisma® Diamond ≈ Gradia® Direct. The highest color change was recorded for Tetric EvoCeram® (∆E00 = 6.0). Additionally, the highest translucency parameter (TP00) and surface roughness before and after immersion in tea were recorded for Tetric EvoCeram®, while the highest decrease in translucency intensity after staining was observed for Gradia® Direct (33%). After repolishing, color changes for Tetric EvoCeram® and N’Durance® remained higher than the clinically acceptable threshold, while the values for Charisma® Diamond and Gradia® Direct were clinically acceptable. Repolishing restored almost complete translucency, fluorescence, and surface roughness, bringing the spectral properties of the composites closer to their initial values. Conclusion. The initial optical characteristics and surface roughness of the composites, as well as their modifications after immersion and repolishing, depend on the type of composite material. The process of staining altered the brightness of the fluorescence, while leaving the spectral shape unaffected. The repolishing procedure almost completely restored the optical properties of all tested composite materials.